Character Education Management in Improving Students' Spiritual Intelligence - Widyatmike Gede Mulawarman; Kundori Kundori; Munir Tubagus; Loso Judijanto; Made Susilawati (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
This research analyses character education management in increasing students' spiritual and spiritual intelligence. The method used is qualitative with a qualitative descriptive design with data collection techniques through observation, interviews, and documentation. Next, data analysis was carried out using a descriptive qualitative study. The research results show that: 1. character education management at SMPN 1 Mojowarno Jombang starts from the planning process, including character education, which is made at the beginning of the school year meeting and involves all stakeholders. The organizing process prepares an organizational structure with its objectives, resources and environment. The implementation process is an action or implementation of a plan crafted carefully and in detail. Implementation is usually carried out after the plan is considered ready. The evaluation process determines the value of everything in the world of education, namely everything related to or occurs in the field of education. 2. Students' spiritual intelligence is awareness of practising the teachings of the Islamic religion, proven by the fact that when it is time for prayer, they immediately do it, as well as discipline, especially in carrying out religious teachings. Manners. Compassion for others, Having empathy and concern for others, Respecting and respecting others. Character education management starts with planning, organizing, implementing, and evaluating.